Potensi Challenge Based Learning dalam Mengembangkan Kemampuan Berpikir Kritis Ditinjau dari Gaya Kognitif Peserta Didik Sekolah Dasar - Angelia, Dita; Purwanto, Agung; Nurjannah, Nurjannah (Social, Humanities, and Educational Studies (SHES): Conference Series, 2025)
Critical thinking is one of the essential 21st-century skills that should be developed from an early age, particularly in elementary education. However, various studies indicate that elementary students' critical thinking skills remain relatively low, partly due to learning models that do not adequately support their development. This article aims to explore the potential of the Challenge Based Learning (CBL) model in enhancing students' critical thinking skills, considering their cognitive styles: Field Independent (FI) and Field Dependent (FD). The literature review shows that CBL promotes active student engagement in solving real-world challenges, which effectively develops critical thinking aspects such as interpretation, analysis, evaluation, and inference. Additionally, cognitive style influences how students respond to learning: FI students tend to be more independent and analytical, while FD students require more guidance and prefer collaborative work. Therefore, implementing CBL with adjustments based on students' cognitive styles holds significant potential for optimizing the development of critical thinking skills.Kemampuan berpikir kritis merupakan salah satu keterampilan esensial abad ke-21 yang perlu dikembangkan sejak pendidikan dasar. Namun, berbagai studi menunjukkan bahwa kemampuan ini masih tergolong rendah, salah satunya disebabkan oleh penerapan model pembelajaran yang kurang mendukung pengembangan berpikir kritis. Artikel ini bertujuan untuk mengkaji potensi model Challenge Based Learning (CBL) dalam meningkatkan kemampuan berpikir kritis peserta didik, dengan mempertimbangkan gaya kognitif Field Independent (FI) dan Field Dependent (FD). Kajian literatur menunjukkan bahwa CBL mampu mendorong keterlibatan aktif siswa dalam memecahkan tantangan nyata sehingga mengembangkan aspek berpikir kritis seperti interpretasi, analisis, evaluasi, dan inferensi. Selain itu, gaya kognitif memengaruhi cara peserta didik merespons pembelajaran: siswa FI cenderung lebih mandiri dan analitis, sementara siswa FD membutuhkan lebih banyak bimbingan dan bekerja lebih baik dalam kolaborasi. Oleh karena itu, penerapan CBL yang disesuaikan dengan gaya kognitif memiliki potensi besar untuk mengoptimalkan pengembangan kemampuan berpikir kritis.